Effect of Ursodeoxycholic Acid Alone and Ursodeoxycholic Acid Plus Domperidone on Radiolucent Gallstones and Gallbladder Contractility in Humans - Ilyas Tuncer; Mustafa Harman; Yasar Colak; Ismail Arslan; M. Kursad Turkdogan (Gastroenterology Research and Practice)
Background/Aims. The aim of this study was to compare the effects of ursodeoxycholic acid (UDCA) alone and UDCA plus domperidone on dissolution of solitary or multiple gallstones. Methods. Fifty-three patients with cholesterol gallstones were randomized into three treatment groups: group I (𝑛=22) was given UDCA (15 mg/kg/day) alone and group II (𝑛=18) was treated with domperidone (30 mg/day) in addition to UDCA. The control group (𝑛=13) was followed without a medical treatment. Gallbladder volumes and ejection fractions were measured sonographically in all patients before and after treatment. Results. After 12 months of treatment, stone dissolution was found in 9 (40.9%) of the patients in group I and 7 (38.8%) of the patients in group II. The difference was statistically significant compared to controls in both treatment groups (𝑃<0.05) but the two groups did not show a difference between each other (𝑃>0.05). All the patients that achieved dissolution had multiple gallstones except for one patient with a solitary stone in group I. Neither monotherapy of UDCA nor the combination with domperidone affected the ejection fraction of gallbladder. Conclusions. Combination with domperidone did not potentiate the efficacy of UDCA. It has been observed that both UDCA alone and UDCA plus domperidone treatment did not affect ejection fraction of gallbladder.